MODELING AND SIMULATION OF SHRIMP DISEASES PROPAGATION IN RIVER NETWORKS AND INSIDE POND - Tuyen, Truong T.T; Hiep, Huynh X; Alexis, Drogoul (Vietnam Journal of Science and Technology, 2012)
ABSTRACT In this paper we study and apply modeling on agent-based simulation for simulating the mechanism of shrimp infection inside shrimp-ponds and on the river networks in the region of Mekong Delta, Vietnam. The disease-propagation rules were established based on the way that the pathogens multiply in water-flows together withother infecting agents such as aquatic or migrating living things. Inside a shrimp-pond, besides the factors mentioned above, the infecting mechanism also depends on the density of shrimps and the initial number of the pathogens. In this study, we constructed two on-river-infecting scenarios for cases of the occurrence or non-occurrence of the pathogens and two inside one shrimp-pond infecting scenarios. All of the results are written in GAML and executed on GAMA platform. Keywords. modeling, agent-based simulation, mechanism of disease-propagation, GAMA platform.